If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(5a + 1) + 3a + 7 = 0 Reorder the terms: 9 + -1(1 + 5a) + 3a + 7 = 0 9 + (1 * -1 + 5a * -1) + 3a + 7 = 0 9 + (-1 + -5a) + 3a + 7 = 0 Reorder the terms: 9 + -1 + 7 + -5a + 3a = 0 Combine like terms: 9 + -1 = 8 8 + 7 + -5a + 3a = 0 Combine like terms: 8 + 7 = 15 15 + -5a + 3a = 0 Combine like terms: -5a + 3a = -2a 15 + -2a = 0 Solving 15 + -2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -2a = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -2a = 0 + -15 -2a = 0 + -15 Combine like terms: 0 + -15 = -15 -2a = -15 Divide each side by '-2'. a = 7.5 Simplifying a = 7.5
| -8h-6h=24 | | 4^3(8^(1/3)z^2 | | 6x+7y=-21 | | 3x+6(2)=x+11(4) | | 6x(2-3y)+7y=-21 | | 3ax-4x=0 | | 23=-3(5y+2) | | 66y/3-34y | | 8x^2-128x=0 | | 1+6y-15y= | | 1/3-K/8=7/24 | | -1(-1y+3)=1 | | -.4x^2+.2x=-2 | | 4x^2+10=-14x | | 2x^3/5=54 | | 3(x+4)+2x=2 | | 11-x=7+3x | | 5(0)-2=4-3(0)+2 | | 24=-3+6(v+7) | | 7(-3)+20=2(-3)+5 | | x^3=6x^2-36x-60 | | 7y^2-7=144 | | 9x^2-74x+16=0 | | -50-2x=-290 | | 6s+7-9s=31 | | X^2+5x+15x=0 | | t-1/3=1/4 | | -300m-4p=10p | | K^1/3/k^2/3k-1 | | 2f+8=3f-4 | | 3/1-√19 | | 2x=y/(y-1)-3 |